Uruguay : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Republic of Uruguay. (IMF Staff Country Reports; Country Report, 2019)
This Article IV Consultation highlights that Uruguay has preserved macroeconomic stability in the wake of the turbulence in the region due to prudent policies and the accumulation of buffers over the years. With the worsening outlook and less friendly external environment, in the near term, policies should focus on maintaining resilience. In this context, additional efforts are needed to put debt on a firm downward trajectory and reduce inflation to within the target band. The IMF staff assesses that the external position is broadly consistent with fundamentals and desirable policy settings. The authorities and IMF staff have remained in broad agreement on the macroeconomic policy objectives, including maintaining public debt on a sustainable trajectory, keeping inflation low, and allowing exchange rate to adjust in line with fundamentals. Fiscal adjustment, however, has not proceeded as quickly as had been originally expected, and inflation has proven difficult to contain within the authorities' target range.